Exploring Financial Literacy Among MSME Owners and Managers: a Narrative Review for Community Pharmacy Measurement - Seraguma, Rahzopan; Widayanti, Anna Wahyuni (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Micro, Small, and Medium Enterprises (MSMEs) were crucial in shaping a nation’s economic landscape, particularly in developing countries. They acted as key drivers of economic development by boosting domestic production and creating job opportunities. However, MSMEs in these regions often faced significant challenges, particularly in accessing adequate financing. This narrative literature review examined the financial literacy of MSME owners and managers and its impact on improving their performance. The review utilized the Science Direct database, focusing on articles published in the last five years within the fields of business, management, accounting, economics, and finance. Only open-access research articles were included. Out of 2,259 articles screened, 2,249 were excluded due to mismatches in topic, methodology, or setting, resulting in 10 papers that aligned with the research focus. The findings highlighted that financial literacy provided entrepreneurs with a deeper understanding of corporate goals and strategies and familiarized MSME owners and managers with various financing options and support services available to them.